2007
DOI: 10.1111/j.1083-6101.2007.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Every Blog Has Its Day: Politically-interested Internet Users’ Perceptions of Blog Credibility

Abstract: This study employs an online survey to examine U.S. politically-interested Internet users' perceptions of the credibility of blogs. The article focuses on the influence of blog reliance compared to motivations for visiting blogs in determining blog credibility. The study found that blogs were judged as moderately credible, but as more credible than any mainstream media or online source. Both reliance and motivations predicted blog credibility after controlling for demographics and political variables. Reliance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 35 publications
12
143
1
5
Order By: Relevance
“…Among their users, political blogs are rated high in believability and depth of information but low on accuracy and fairness (Johnson et al, 2008). Several studies have compared the credibility of blogs to other sources of political information, with mixed results that become coherent when considering characteristics of the evaluator.…”
Section: Blogsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among their users, political blogs are rated high in believability and depth of information but low on accuracy and fairness (Johnson et al, 2008). Several studies have compared the credibility of blogs to other sources of political information, with mixed results that become coherent when considering characteristics of the evaluator.…”
Section: Blogsmentioning
confidence: 99%
“…Several studies have compared the credibility of blogs to other sources of political information, with mixed results that become coherent when considering characteristics of the evaluator. Those who rely heavily on blogs for political information judge them to be highly credible, even more so than either traditional media sources or online sources of political information such as candidate and issue websites or political chat rooms (Johnson and Kaye, 2004;Johnson et al, 2008;Johnson and Kaye, 2009; see also Banning and Sweetser, 2007). However, studies that have used either representative samples or more broad student samples find that blogs are rated lower in credibility than traditional media (Meyer, Marchionni, and Thorson, 2010;Thorson, Vraga, and Ekdale, 2010;Metzger et al, 2011).…”
Section: Blogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los predictores más importantes de la credibilidad, siempre según los autores, serían las variables políticas, tales como el conocimiento político, el interés hacia la política, la confianza en la política y la participación política. Johnson et al (2007) han descubierto que los usuarios de Internet políticamente interesados confían más en los blogs que en cualquier otra fuente de información y que los perciben como más creíbles respecto a las páginas web de los periódicos o que las televisiones online. y contestar tanto a los posts de los autores como a las intervenciones de los demás usuarios, aunque no todos los blogs lo permitan o algunos requieran registro previo (Gil de Zuñiga et al, 2009).…”
Section: Determinantes Del Uso De Los Blogs Políticosunclassified
“…Research into internet users has identified convenience, a sense of community and information seeking as the major reasons for visiting blogs [25]. The impacts of blogging can also be behaviourally empowering and tie in with intrinsic motivations [26], as well as providing a cathartic space to process difficult emotions [27].…”
Section: Introductionmentioning
confidence: 99%